neuralized encodes a peripheral membrane protein involved in delta signaling and endocytosis. - Pavlopoulos, E.; Pitsouli, C.; Klueg, K.M.; Muskavitch, M.A.; Moschonas, N.K.; Delidakis, C. (Developmental Cell, 2001)
Activation of the Notch (N) receptor involves an intracellular proteolytic step triggered by shedding of the extracellular N domain (N-EC) upon ligand interaction. The ligand Dl has been proposed to effect this N-EC shedding by transendocytosing the latter into the signal-emitting cell. We find that Dl endocytosis and N signaling are greatly stimulated by expression of neuralized (neur). neur inactivation suppresses Dl endocytosis, while its overexpression enhances Dl endocytosis and Notch-dependent signaling. We show that neur encodes an intracellular peripheral membrane protein. Its C-terminal RING domain is necessary for Dl accumulation in endosomes, but may be dispensable for Dl signaling. The potent modulatory effect of Neur on Dl activity makes Neur a candidate for establishing signaling asymmetries within cellular equivalence groups.